English Math For Young Learners Based on Nature (EMYLBON) sebagai Upaya Penguatan Kompetensi Guru - Arta Ekayanti; Ana Maghfiroh; Betty Yulia Wulansari (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This program aims to provide support for strengthening teacher competence in mathematics, English, and nature-based learning. This activity was packaged in workshops and training programs. The results of this activity indicated a positive effect on the competence of the participants. This program can elevate the participants' understanding. There was a significant increase in understanding scores, on average, from 68.75 to 88.08. In other words, there was an increase of 28.12%, of course this was quite a large value. In addition, the responses of the participants were also quite good. 74.17 agreed and 25.83 stated strongly agree on the aspects asked. This indicated that the participants gain benefits from this program